Kinetics of liver macrophages (Kupffer cells) in SIV-infected macaques - Ahsan, Muhammad H. (2013)
Since the liver drains antigens from the intestinal tract, and since the intestinal tract is a major site of viral replication, we examined the dynamics of liver macrophages (Kupffer cells) throughout SIV infection. Absolute numbers of Kupffer cells increased in the livers in acute infection, and in animals with AIDS. Significantly higher percentages of proliferating (BrdU+) Kupffer cells were detected in acute infection and in AIDS with similar trends in blood monocytes. Significantly higher percentages of apoptotic (AC3+) Kupffer cells were also found in acute and AIDS stages. However, productively infected cells were not detected in liver of 41/42 animals examined, despite abundant infected cells in gut and lymph nodes of all animals. Increased rates of Kupffer cell proliferation resulting in an increase in Kupffer cells without productive infection indicate SIV infection affects Kupffer cells, but the liver does not appear to be a major site of productive viral replication.